2013
DOI: 10.1021/es4012383
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Sharp Oxalate Reductions in Stratocumulus Clouds at Variable Altitudes: Organic Acid and Metal Measurements During the 2011 E-PEACE Campaign

Abstract: This work examines organic acid and metal concentrations in northeastern Pacific Ocean stratocumulus cloudwater samples collected by the CIRPAS Twin Otter between July and August 2011. Correlations between a suite of various monocarboxylic and dicarboxylic acid concentrations are consistent with documented aqueous-phase mechanistic relationships leading up to oxalate production. Monocarboxylic and dicarboxylic acids exhibited contrasting spatial profiles reflecting their different sources; the former were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 94 publications
11
104
0
Order By: Relevance
“…Eighty one samples had sufficient volume for elemental and ionic composition analysis. One fraction of the liquid volumes was analyzed with inductively coupled plasma mass spectrometry (ICP-MS), details of which are provided by Sorooshian et al (2013). The reported measurements of all elements in each sample represent the average of three measurements.…”
Section: Aircraft Measurementsmentioning
confidence: 99%
“…Eighty one samples had sufficient volume for elemental and ionic composition analysis. One fraction of the liquid volumes was analyzed with inductively coupled plasma mass spectrometry (ICP-MS), details of which are provided by Sorooshian et al (2013). The reported measurements of all elements in each sample represent the average of three measurements.…”
Section: Aircraft Measurementsmentioning
confidence: 99%
“…They may then be oxidized in the particle aqueous phase to produce OxA (Warneck, 2003), which can then react with mineral ions in the particle to produce insoluble material (e.g., calcium oxalate), reducing particle hygroscopicity. OxA has also been found to be significant in particles dominated by non-hygroscopic material (e.g., mineral dust) (Sullivan and Prather, 2007). For these particles, solubilizing reactions, such as uptake of nitric acid, may occur at the particle surface, and subsequent water exposure creates conditions ripe for reaction between OxA and di-valent cations (Laskin et al, 2012).…”
Section: G Drozd Et Al: Inorganic Salts Interact With Organic Di-acidsmentioning
confidence: 99%
“…Since the contribution of sea salt (or other mineral salts) in submicron particles at continental forest sites far from the sea is minor (Saarikoski et al, 2005), ammonium or aminium salts are likely main contributors to the growth of aerosol particles, even at sub-20 nm sizes (Barsanti et al, 2009;Smith et al, 2010). However, at marine sites or other mineral-rich areas the contribution of organic salts from mineral-salt-organicacid reactions may have a significant effect on aerosol chemical properties and further cloud processing (Furukawa and Takahashi, 2011;Laskin et al, 2012;Rinaldi et al, 2011; G. Drozd et al: Inorganic salts interact with organic di-acids 5207 Sorooshian et al, 2013). These results emphasize the fact that atmospheric species, both organic and inorganic, can undergo drastic changes when they react with each other and these changes can alter the chemical and physical properties of particles.…”
Section: G Drozd Et Al: Inorganic Salts Interact With Organic Di-acidsmentioning
confidence: 99%
“…Results showed that there was a significant good correlation (p < 0.05, R > 0.5, n = 8) between dissolved iron (Fe(II) and Fe(TD)) and sulfate in the coarse mode, but there was no good correlation between dissolved iron and oxalate in both mode, which may result from the low concentration of oxalate in the ambient environment. Sorooshian et al (2013) [59] conducted filed work in northeastern Pacific Ocean by collecting stratocumulus cloud water and examining the organic acid and metal concentrations; they found an inverse relationship between oxalate and Fe. Thus, the oxalate sink in this study could be explained to some extent by the photolysis of iron oxalato complexes.…”
Section: Acid Processingmentioning
confidence: 99%